Facile synthesis of SnS nanostructures with different morphologies for supercapacitor and dye-sensitized solar cell applications - Dar, Mohd Arif; Govindarajan, D.; Dar, Gulam Nabi (Journal of materials science. Materials in electronics, 2021)
In this paper, tin Sulfide (SnS) nanoparticles are synthesized with three different solvents through hydrothermal method and characterized by using X-ray diffraction, scanning electron microscopy, UV-DRS spectroscopy, Fourier transform infrared spectroscopy, energy-dispersive X-ray spectrum, supercapacitor, and photovoltaic performance. XRD patterns indicate that the prepared SnS nanoparticles exist in the orthorhombic phase. The SEM analysis clearly picturizes the morphological changes in the SnS nanoparticles synthesized through different solvents. The UV-DRS spectrum gives direct energy band gap which lies between 1.0 and 2.0 eV. The FT-IR spectrum explains various functional groups present in the SnS nanoparticles. The prepared SnS counter electrodes (CEs) showed good electrocatalytic activity in the redox reaction of the I − /I3 − . The efficiency of tin sulfide prepared in ethanol (SnS-e), tin sulfide prepared in acetone (SnS-a), and tin sulfide prepared in methanol (SnS-m) counter electrodes (CEs) are 9.99%, 9.90%, and 9.86% in Dye-sensitized solar cells (DSSC) than that of platinum counter electrode which is 9.80%. The specific capacitance of 284 F/g is obtained for SnS-e electrode at a current density of 5 A/g and an energy density of 216 Wh/kg corresponding to power density value of 1.6 KWh/kg which proves SnS-e electrode possesses better capacitive performance than SnS-a and SnS-m electrodes, respectively.